PROJETO ESCOLA ATIVA NO MARANHÃO: a prática pedagógica dos professores e supervisores no município de Viana - Souza, Angélica Maria Frazão de (2009)
This paper investigates teachers and supervisors pedagogical practices from multi-seriate classes in High School of Escola Viva Project in Viana-Maranhão. The schools which take part in this research are assisted by Education Municipal Department and they are located in rural area in Viana City. The individuals involved in this research are: teachers, supervisors and coordinators who work in these classes. It was used for data collection, semi-structured interviews analysis and questionnaires. In pedagogical practice analysis of Escola Ativa Project , the aspects covered are: working conditions, training, teachers and supervisors pedagogical experience and routine, as well as analysis and evaluation of Escola Ativa Project . In order to define categories or aspects to be analyzed, theories of several authors were studied, such as: John Dewey, Durkheim, Bourdieu, Passeron and Althusser, and finally Baudelot, Establet and particularly Antonio Gramsci to contrast with education reproducible view.